2014
DOI: 10.1016/j.ijsu.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The first case of acinic cell carcinoma of the breast within a fibroadenoma: Case report

Abstract: A case of acinic cell carcinoma of the breast is reported in a 26-year-old woman. She presented a lump in her right breast, that seemed to be a fibroadenoma. The open biopsy revealed a well-bordered fibroadenoma, together with a proliferation of cells characterized by serous acinar differentiation and eosinophilic cytoplasmic granules. Tumor cells stained for amylase, lysozyme, α-1-antichymotripsin, epithelial membrane antigen, S-100 protein, pan-cytokeratin, cytokeratin 7 and E-cadherin. Estrogen receptor, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A detailed morphologic description was provided in 31 of these cases [1,4,725]. Shimao et al [9] reported the only case of breast AcCC to date occurring in a male patient.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed morphologic description was provided in 31 of these cases [1,4,725]. Shimao et al [9] reported the only case of breast AcCC to date occurring in a male patient.…”
Section: Resultsmentioning
confidence: 99%
“…AcCCs of the breast are extremely rare. Only 39 cases have been described in the English literature to date, usually as case reports or small case series . In addition to immunoreactivity for serous differentiation markers, AcCCs of the breast have been reported to display a triple‐negative phenotype; interestingly, however, at variance with the common forms of triple‐negative breast cancer (TNBC), breast AcCCs are reported to have indolent clinical behaviour …”
Section: Introductionmentioning
confidence: 99%
“…ACC affects mainly adult women, with only 1 male patient reported in the literature [74]. ACC can arise in any breast quadrants, presenting as an infiltrative nodule; size varies sometimes reaching large dimensions [75,76]. One case of ACC arising in a fibroadenoma was reported [76].…”
Section: Acinic Cell Carcinoma (Acc)mentioning
confidence: 99%